2021
DOI: 10.1021/acs.cgd.1c00644
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Optimization of Bi2Se3 Thin Films for Enhanced Thermoelectric Performance

Abstract: Vapor–solid growth (VSG) is a cost-effective technique to synthesize Bi2Se3 materials with promising thermoelectric (TE) performance. In this work, smooth Bi2Se3 thin films with enhanced TE performance have been realized through regulating the carrier gas flow rate during the VSG process. The optimized morphology improves the electrical conductivity and decouples its interplay withthe Seebeck coefficient in Bi2Se3. As a result, our Bi2Se3 synthesized at 150 sccm gas flow rate exhibited a Seebeck coefficient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…This method offers a means to quantify the total broadening of the material, encapsulating both size effects and microstrain contributions. By integrating these factors, the Williamson−Hall method offers a more nuanced understanding of the structural characteristics of nanomaterials, 30 = + total size strain (4) where β total is the total broadening, β size is the broadening due to the crystallite size, and β strain is the broadening due to strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This method offers a means to quantify the total broadening of the material, encapsulating both size effects and microstrain contributions. By integrating these factors, the Williamson−Hall method offers a more nuanced understanding of the structural characteristics of nanomaterials, 30 = + total size strain (4) where β total is the total broadening, β size is the broadening due to the crystallite size, and β strain is the broadening due to strain.…”
Section: Resultsmentioning
confidence: 99%
“…The optimization of the surface morphology with low surface roughness improves the electrical conductivity of Bi 2 Se 3 with high thermoelectrical performance in nanodevices. 4 The orthorhombic phase of Bi 2 Se 3 is considered to be an n-type semiconductor, and its optoelectronic properties are used in photosensitive devices. On the other hand, a small band gap is found for its rhombohedral phase in the form of a topological insulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[35][36][37] The morphology optimization for thermoelectric materials is an effective method to improve thermoelectric performance. 38,39 Q. Chen et al reported morphology optimization of Bi 2 Se 3 thin film to enhance thermoelectric performance via VSG process. 38 Z. Shi et al reported synthesis plate-like Ca 3 Co 4 O 9 microcrystal particles and its improved thermoelectric performances.…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Q. Chen et al reported morphology optimization of Bi 2 Se 3 thin film to enhance thermoelectric performance via VSG process. 38 Z. Shi et al reported synthesis plate-like Ca 3 Co 4 O 9 microcrystal particles and its improved thermoelectric performances. 39 In this study, we controlled the morphology of Cu 3 SbSe 4 using exfoliated Se nanosheets.…”
Section: Introductionmentioning
confidence: 99%